(untitled) (Global Journal of Sciences, 2025)
Over the past few years, environmental challenges and the impacts of climate change have gained significant attention among policymakers and energy experts. Conforming to the objectives outlined in Sustainable Development Goals 7 and 13, which underscore the importance of clean energy provision and climate change mitigation, this study aligns with the sustainability targets set forth in Vision 2030. The research explores the intricate relationships among financial development, the stringency of environmental policies, advancements in information and communication technology (ICT), human capital, and economic growth. It aims to understand their combined effects on sustainable energy in the United States from the initial quarter of 1990 to the concluding quarter of 2020. Employing quantile-based methods including multivariable quantile-on-quantile regression (MQQR) and non-parametric quantile causality, our research reveals a positive influence across all quantiles for financial development, economic growth, environmental policy stringency, ICT innovations, and human capital on sustainable energy. Additionally, our quantile causality analysis confirms these factors significantly predict sustainable energy in the United States. These findings form the basis for policy recommendations.